2007
DOI: 10.1007/s00531-007-0270-3
|View full text |Cite
|
Sign up to set email alerts
|

Life inhabits rocks: clues to rock erosion from electron microscopy of pisolite at a UNESCO heritage site in Brazil

Abstract: Rock erosion is attracting increasing attention from scientists worldwide. The area encompassing the Saint John Baptist Church, Saint John Village, XVII century ruins in Rio Grande do Sul at the UNESCO World Heritage Site is considered a Brazilian treasure. However, the risk of damage to this site from rock erosion has recently increased tremendously. Generally, the rocky construction such as fence, wall and tomb stone, seems strong but is actually extremely sensitive to erosion caused by lichens, fungi, molds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Sterfl inger e Pinar (2013) sugeriram que os fungos poderiam ser os microrganismos mais importantes envolvidos na degradação da pedra, mas também é sabido que as cianobactérias podem penetrar e crescer nas rochas (Gaylarde et al, 2012), obviamente causando danos � sicos apenas pela presença deles. No entanto, a capacidade das cianobactérias de solubilizar metabolicamente e depois permi� r ou causar a� vamente a redefi nição e realocação de minerais está bem documentada em crostas de sal (Canfora et al, 2016), bem como em edi� cios de arenito e itacuru, um � po de rocha rica em ferro usada nas missões jesuítas na América do Sul (Tazaki et al, 2009;Barrionuevo et al, 2016). As bainhas gela� nosas de cianobactérias fi lamentosas e esféricas são consideradas locais de nucleação de depósitos de cálcio (Gerbersdorf e Wieprecht, 2015), e as cianobactérias detectadas nas amostras deste estudo também poderiam ser, pelo menos em parte, responsáveis pelos abundantes cristais de calcita encontrados, assim como os fungos fi lamentosos (Bindschedler et al, 2016).…”
Section: Figura 3 Micrografi As Sem De Crostas Negras Mostrando (A E B)unclassified
“…Sterfl inger e Pinar (2013) sugeriram que os fungos poderiam ser os microrganismos mais importantes envolvidos na degradação da pedra, mas também é sabido que as cianobactérias podem penetrar e crescer nas rochas (Gaylarde et al, 2012), obviamente causando danos � sicos apenas pela presença deles. No entanto, a capacidade das cianobactérias de solubilizar metabolicamente e depois permi� r ou causar a� vamente a redefi nição e realocação de minerais está bem documentada em crostas de sal (Canfora et al, 2016), bem como em edi� cios de arenito e itacuru, um � po de rocha rica em ferro usada nas missões jesuítas na América do Sul (Tazaki et al, 2009;Barrionuevo et al, 2016). As bainhas gela� nosas de cianobactérias fi lamentosas e esféricas são consideradas locais de nucleação de depósitos de cálcio (Gerbersdorf e Wieprecht, 2015), e as cianobactérias detectadas nas amostras deste estudo também poderiam ser, pelo menos em parte, responsáveis pelos abundantes cristais de calcita encontrados, assim como os fungos fi lamentosos (Bindschedler et al, 2016).…”
Section: Figura 3 Micrografi As Sem De Crostas Negras Mostrando (A E B)unclassified
“…XRF was one of a range of techniques applied and results showed that although a few trace elements were relatively immobile, many major and trace elements (particularly Ca and Na) were mobile from the beginning of granite weathering, effects that were associated with the breakdown of plagioclase and dissolution of biotite. A related form of degradation that leads to rock erosion is the effect of lichens, fungi, molds and bacteria on rock surfaces, a phenomenon that was studied by Tazaki et al 193 at the UNESCO World Heritage Site of Saint John Baptist Church, Rio Grande do Sul, Brazil. XRF was again one of the techniques (the others were TEM and STEM) used to study samples from a collapsed wall in the ancient church and showed that the pistolitic laterite surface was inhabited by lichens and fungi that effectively formed a bio-claymineralised surface dominated by the minerals goethite and kaolinite.…”
Section: Geological and Industrial Mineralsmentioning
confidence: 99%
“…Given the lack of evidence for nearby lateritic or plinthitic soils during this period, coeval Iberian volcanism is the most plausible source of iron. (Jeans et al 2000); 3 5 Indonesian iron ooids (Sturesson et al 2000); 4 5 Ejpovice iron ooids and volcanic rocks (Sturesson 2003); 5 5 Oxfordian Betic plinthitic iron ooids type A (Reolid et al 2008); 6 5 Sta Augusta laterites (Morey and Setterholm 1997); 7 5 Brazilian pisoids (Tazaki et al 2009); 8 5 Chondrite (Taylor and McLennan 1985); 9 5 PAAS (Taylor and McLennan 1985).…”
Section: Geochemical Inferencesmentioning
confidence: 99%